Challenges Facing Women's Leadership in the ‎Educational Sector as Determinants of ‎Psychological Capital in Negev Region - Abu Hammad, Taleb; Shqairat ‎, Tahani; Al-Jondi, Nabil (Jordan Journal of Educational Sciences, 2024)
Study aimed to identify the challenges facing women’s leadership in the educational sector as determinants of psychological capital in the Negev region. The quantitative research approach was used, and the questionnaire served as the identification tool. A scale was created to categorize and confine the obstacles into four distinct dimensions: ideological, social, economic, and challenges related to policies, regulations, and laws. The study examined four dimensions of psychological capital, namely self-efficacy, resilience, hope, and flexibility. Each dimension was discussed in six items. The validity of these dimensions was then verified, and their implications were explored. Finally, the study applied these dimensions to a sample of 922 women in leadership positions in Badia. The findings indicated that female leaders in Bedouin society encounter moderate challenges and that psychological capital is also at a moderate level. Furthermore, the study revealed that the independent variables (ideological challenges, social challenges, and economic challenges) have a statistically significant impact on psychological capital. The study emphasized the significance of including Arab Bedouin women leaders in training programs to enhance their skills, qualify them for leadership roles, and address the gaps in their knowledge and societal understanding of psychological capital